Synthesis, electronic properties and self-assembly on Au{111} of thiolated (oligo)phenothiazines - Franz, Adam W (Beilstein-Institut, 2010)
(Oligo)phenothiazinyl thioacetates, synthesized by a one-pot sequence, are electrochemically oxidizable and highly fluorescent. SAMs can be readily formed from thiols prepared by in situ deprotection of the thioacetates in the presence of a gold-coated silicon wafer. Monolayer formation is confirmed by ellipsometry and the results compared to those obtained by force field and DFT calculations.